Using the 3D body scanner in elite sports - Schüler, A.; Fichtner, I.; Ueberschär, O. (Proc. of 3DBODY.TECH 2018 - 9th Int. Conf. and Exh. on 3D Body Scanning and Processing Technologies, 2018)
Using laser-based 3D body scanners in elite sports may offer a decisive advantage with respect to individual motion optimization and training. In the following, a brief overview of various applications of 3D body scanning in elite sports will be given as employed at the Institute for Applied Training Science. In many artistic sports, such as figure skating, gymnastics or diving, high rotation speeds for twists and somersaults are required for successful competition performance. To achieve those high angular velocities in air, athletes must adopt minimal moments of inertia (MOI) with respect to the rotational axis. 3D body scanners can easily be used to measure MOI and detect even small changes between different individual postures. Thus, optimal individual rotation positions for twists and somersaults can be determined. Five straight positions and four tucked positions were compared with respect to their MOI around the longitudinal and mediolateral axes, respectively. Compared to the standard up-right standing position, we were able to show that a straight position with forearms crossed in front of the chest yields a 12 % smaller MOI for the longitudinal axis. Regarding the mediolateral axis, a face-down tucked position generates an up to 30 % smaller MOI than a face-up tucked position. Moreover, for figure skating not only an optimal arm position but also closing the knees and twisting the shoulder and hip portions contribute to a significant decrease in MOI. In ski jumping and snowboard cross, on the other hand, minimal aerial drag is a key performance factor. Employing 3D body scanner measurements there, aerodynamically unsuitable clothing can be identified. For ski jumping, 3D scans can also be used to reveal disadvantageous in-run postures, e.g. too big knee angles or aerodynamically suboptimal head, back or hand positions. Finally, anthropometric data of athletes as derived from body scanner measurements are also used for purposes of motion analysis and biomechanical simulations.